Anti‐Müllerian hormone and risk of ovarian cancer in nine cohorts. Issue 2 (4th October 2017) - Jung, Seungyoun; Allen, Naomi; Arslan, Alan A.; Baglietto, Laura; Barricarte, Aurelio; Brinton, Louise A.; Egleston, Brian L.; Falk, Roni T.; Fortner, Renée T.; Helzlsouer, Kathy J.; Gao, Yutang; Idahl, Annika; et al.
Abstract : Animal and experimental data suggest that anti‐Müllerian hormone (AMH) serves as a marker of ovarian reserve and inhibits the growth of ovarian tumors. However, few epidemiologic studies have examined the association between AMH and ovarian cancer risk. We conducted a nested case‐control study of 302 ovarian cancer cases and 336 matched controls from nine cohorts. Prediagnostic blood samples of premenopausal women were assayed for AMH using a picoAMH enzyme‐linked immunosorbent assay. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using multivariable‐adjusted conditional logistic regression. AMH concentration was not associated with overall ovarian cancer risk. The multivariable‐adjusted OR (95% CI), comparing the highest to the lowest quartile of AMH, was 0.99 (0.59–1.67) (Ptrend : 0.91). The association did not differ by age at blood draw or oral contraceptive use (all P heterogeneity : ≥0.26). There also was no evidence for heterogeneity of risk for tumors defined by histologic developmental pathway, stage, and grade, and by age at diagnosis and time between blood draw and diagnosis (all P heterogeneity : ≥0.39). In conclusion, this analysis of mostly late premenopausal women from nine cohorts does not support the hypothesized inverse association between prediagnostic circulating levels of AMH and risk of ovarian cancer. Abstract : What's new? As the anti‐Müllerian hormone (AMH) inhibits Müllerian duct formation during sexual differentiation, an inhibitory role of the AMH in ovarian cancer development was proposed. Here the authors performed a pooled analysis of nine cohorts of mostly late premenopausal women testing a potential protective role of AMH against ovarian carcinogenesis. Contrary to animal and experimental studies, the authors found no associations between AMH and ovarian cancer risk, pointing to future studies in younger women with overall higher AMH concentrations to conclusively establish whether AMH reduces ovarian cancer risk.